Relationship between schizophrenic symptoms and verbal memory impairment: a metaanalysis - Nieznański, Marek (Studia Psychologica: Theoria et praxis, 2004)
This article presents meta-analyses of the studies that reported correlational data for the relations between symptom dimensions in schizophrenia and performance in tests of verbal memory. The results showed statistically significant relationships of negative symptoms with verbal recall. Verbal memory measures also showed a significant correlation with disorganization symptoms, but not with hallucinations and delusions. The findings revealed significant effects of some moderator variables, especially duration of illness and gender. The article also emphasises the role of medication side effects and depressive symptoms in verbal memory impairment in schizophrenia.